2021
DOI: 10.1371/journal.pone.0255081
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability of stock price fluctuations: Explanation from a recursive dynamic model

Abstract: The sustainability of stock price fluctuations indicated by many empirical studies hardly reconciles with the existing models in standard financial theories. This paper proposes a recursive dynamic asset pricing model based on the comprehensive impact of the sentiment investor, the information trader and the noise trader. The dynamic process of the asset price is characterized and a numerical simulation of the model is provided. The model captures the features of the actual stock price that are consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Paul and Frank found through their study that growth was associated with stock market booms and was positively correlated [9]. Xie, Xia and Gao found that investor sentiment is a key factor influencing large fluctuations in stock prices, while asset prices affected by investor sentiment always overreact [10]. Mbutor found that: exchange rate fluctuations have a strong impact on the all-stock index, and a decline in the volume of bank loans can also cause a decline in stock prices [11].…”
Section: Research On the Factors Influencing Stock Price Volatilitymentioning
confidence: 96%
“…Paul and Frank found through their study that growth was associated with stock market booms and was positively correlated [9]. Xie, Xia and Gao found that investor sentiment is a key factor influencing large fluctuations in stock prices, while asset prices affected by investor sentiment always overreact [10]. Mbutor found that: exchange rate fluctuations have a strong impact on the all-stock index, and a decline in the volume of bank loans can also cause a decline in stock prices [11].…”
Section: Research On the Factors Influencing Stock Price Volatilitymentioning
confidence: 96%
“…On the theoretical side, some asset pricing models have been developed to support the role of investor sentiment, such as Mendel and Shleifer [ 20 ], Yan [ 21 ], Xie et al [ 22 ], Gao et al [ 23 ], Yang and Gao [ 24 ], Yang and Zhang [ 25 , 26 ], Yang and Li [ 27 , 28 ] demonstrated this view. Mendel and Shleifer [ 20 ], Yan [ 21 ], Xie et al [ 22 ] constructed asset pricing model that includes noise traders, their model illustrated the influence of noise on the stock price.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, some asset pricing models have been developed to support the role of investor sentiment, such as Mendel and Shleifer [ 20 ], Yan [ 21 ], Xie et al [ 22 ], Gao et al [ 23 ], Yang and Gao [ 24 ], Yang and Zhang [ 25 , 26 ], Yang and Li [ 27 , 28 ] demonstrated this view. Mendel and Shleifer [ 20 ], Yan [ 21 ], Xie et al [ 22 ] constructed asset pricing model that includes noise traders, their model illustrated the influence of noise on the stock price. For example, Mendel and Shleifer [ 20 ] presented a chase noise model that most rational but uninformed traders occasionally chase noise as if it were information, thereby amplifying the sentiment shocks on prices, leading to a small number of noise traders can have a great impact on market equilibrium disproportionate to their size in the market.…”
Section: Introductionmentioning
confidence: 99%